C-Terminal Domain of Hemocyanin, a Major Antimicrobial Protein from Litopenaeus vannamei: Structural Homology with Immunoglobulins and Molecular Diversity - Zhang, Yue-Ling; Peng, Bo; Li, Hui; Yan, Fang; Wu, Hong-Kai; Zhao, Xian-Liang; Lin, Xiang-Min; Min, Shao-Ying; Gao, Yuan-Yuan; Wang, San-Ying; Li, Yuan-You; Peng, Xuan-Xian (Frontiers in Immunology, 2017)
Invertebrates rely heavily on immune-like molecules with highly diversified variability so as to counteract infections. However, the mechanisms and the relationship between this variability and functionalities are not well understood. Here, we showed that the C-terminal of hemocyanin (HMC) from shrimp Litopenaeus vannamei contained an evolutionary conserved domain with highly variable genetic sequence, which is structurally homologous to immunoglobulin. This domain is responsible for recognizing and binding to bacteria or red blood cells, initiating agglutination and hemolysis. Furthermore, when HMC is separated into three fractions using anti-human IgM, IgG or IgA, the sub-population, which reacted with anti-human IgM (HMC-M), showed the most significant antimicrobial activity. The high potency of HMC-M is a consequence of glycosylation, as it contains high abundance of α-D-mannose relative to α-D-glucose and N-acetyl-D-galactosamine. Thus, the removal of these glycans abolished the antimicrobial activity of HMC-M. Our results present a comprehensive investigation of the role of HMC in fighting against infections through genetic variability and epigenetic modification.